A high energy phosphate jump - From pyrophospho-inositol to pyrophospho-serine. (January 2020) - Ganguli, Shubhra; Shah, Akruti; Hamid, Aisha; Singh, Arpita; Palakurti, Ravichand; Bhandari, Rashna
Abstract: Inositol pyrophosphates (PP-IPs) are a class of energy rich metabolites present in all eukaryotic cells. The hydroxyl groups on these water soluble derivatives of inositol are substituted with diphosphate and monophosphate moieties. Since the discovery of PP-IPs in the early 1990s, enormous progress has been made in uncovering pleiotropic roles for these small molecules in cellular physiology. PP-IPs exert their effect on proteins in two ways – allosteric regulation by direct binding, or post-translational regulation by serine pyrophosphorylation, a modification unique to PP-IPs. Serine pyrophosphorylation is achieved by Mg 2+ -dependent, but enzyme independent transfer of a β-phosphate from a PP-IP to a pre-phosphorylated serine residue located in an acidic motif, within an intrinsically disordered protein sequence. This distinctive post-translational modification has been shown to regulate diverse cellular processes, including rRNA synthesis, glycolysis, and vesicle transport. However, our understanding of the molecular details of this phosphotransfer from pyrophospho-inositol to generate pyrophospho-serine, is still nascent. This review discusses our current knowledge of protein pyrophosphorylation, and recent advances in understanding the mechanism of this important yet overlooked post-translational modification.